Synthesis, Crystal Structure, and DFT Study of Ethyl 1-(2-(Hydroxyimino)-2-phenylethyl)-3-phenyl-1H-pyrazole-5-carboxylate - Jin-Hui Zhou; Liang-Wen Zheng; Mao-Cai Yan; Mao-Jian Shi; Jing Liu; Guo-Qiang Shangguan (Journal of Chemistry)
The crystal structure of ethyl 1-(2-(hydroxyimino)-2-phenylethyl)-3-phenyl-1H-pyrazole-5-carboxylate has been determined by X-ray single crystal diffraction. The crystal of the title compound is the monoclinic space group P2/c with unit cell parameters of a=8.634(2) Å, b=9.616(2) Å, c=22.190(3) Å, β=99.2652°, V=1818.3(4) Å3, and Z=4. The dihedral angles formed by the planes of the central pyrazole ring and the adjacent benzene rings are 73.60(7)° and 3.55(7)°, respectively. The combination of the weak intermolecular C-H⋯O and N-H⋯O hydrogen-bonding interactions stabilizes the crystal packing. The geometries of its Z and E isomers and the corresponding transition state (TS), as well as the dimer of its Z isomer, are optimized using the B3LYP hybrid functional coupled with def-TZVP triple-zeta polarized basis set. The bond angles and bond lengths of the optimized structure of Z dimer are very consistent with those of its single crystal parameters. Double-hybrid functional PWPB95-D3 in combination with very highly accurate basis set def2-QZVP is employed to evaluate accurate energy of each isomer and TS. The calculated equilibrium constant between Z and E isomers corresponds to the [Z]/[E] ratio of 4.29. Mulliken atomic charges and electrostatic potential (ESP) on molecular van der Waals (vdW) surface are calculated in order to study and predict the intermolecular interactions. The molecular total energies and frontier orbital analysis are also discussed.